2016
DOI: 10.1039/c6ob00067c
|View full text |Cite
|
Sign up to set email alerts
|

A three-component reagent system for rapid and mild removal of O-, N- and S-trityl protecting groups

Abstract: A new reagent system consisting of a Lewis acid such as BF3·Et2O or Cu(OTf)2, the mild protic acid hexafluoroisopropanol and the reducing quenching agent triethylsilane was elaborated for O-, N- and S-detritylation of nucleoside, carbohydrate and amino acid derivatives. The method is compatible with acetyl, silyl, acetal and Fmoc groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Figure 2 depicts selected ROESY and NOESY correlations that corresponding to configurations at C 3 , C 7 and C 9 centers of representative compounds 7 SSS (1,5) and 7 RRR (2,2). In addition, NMR spectroscopic analysis of the mixture of 7 SRS/SSS (2,2) indicated that the minor diastereoisomer was structurally equivalent to compound 7 SSS (2,1), which had been synthesized from 4 SS (2,1) (see Supporting information), which thus proves the S configuration of the C 3 stereocenter. More specifically, application of the previously reported synthetic method [55] for the reaction of Fmoc-L-Ser(tBu)-OH 1 S , 2-bromo-1-(p-tolyl)ethan-1-one 2(2) and Fmoc-D-Ala-OH 3 R (2) or Fmoc-D-Ser(tBu)-OH 1 R , 2-bromo-1-(p-tolyl)ethan-1-one 2(2) and Fmoc-L-Ala-OH 3 S (1) led to very low conversions rate of intermediates 4, and acylation with Fmoc-D-Ala-OH/Fmoc-L-Ala-OH had to be repeated three times to reach quantitative conversion.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Figure 2 depicts selected ROESY and NOESY correlations that corresponding to configurations at C 3 , C 7 and C 9 centers of representative compounds 7 SSS (1,5) and 7 RRR (2,2). In addition, NMR spectroscopic analysis of the mixture of 7 SRS/SSS (2,2) indicated that the minor diastereoisomer was structurally equivalent to compound 7 SSS (2,1), which had been synthesized from 4 SS (2,1) (see Supporting information), which thus proves the S configuration of the C 3 stereocenter. More specifically, application of the previously reported synthetic method [55] for the reaction of Fmoc-L-Ser(tBu)-OH 1 S , 2-bromo-1-(p-tolyl)ethan-1-one 2(2) and Fmoc-D-Ala-OH 3 R (2) or Fmoc-D-Ser(tBu)-OH 1 R , 2-bromo-1-(p-tolyl)ethan-1-one 2(2) and Fmoc-L-Ala-OH 3 S (1) led to very low conversions rate of intermediates 4, and acylation with Fmoc-D-Ala-OH/Fmoc-L-Ala-OH had to be repeated three times to reach quantitative conversion.…”
Section: Resultsmentioning
confidence: 92%
“…For this purpose, Fmoc-D-Ser(tBu)-OH 1 R , 2-bromo-1-(ptolyl)ethan-1-one 2(2) and Fmoc-D-Ala-OH 3 R (2) were used to synthesize intermediate 4 RR (2,2). For this purpose, Fmoc-D-Ser(tBu)-OH 1 R , 2-bromo-1-(ptolyl)ethan-1-one 2(2) and Fmoc-D-Ala-OH 3 R (2) were used to synthesize intermediate 4 RR (2,2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations